DIMENSI KEKUASAAN DALAM NOVEL NEGERI SENJA KARYA SENO GUMIRA AJIDARMA PERSPEKTIF MICHEL FOUCAULT - Satriani, Irma (Hasta Wiyata, 2024)
This study aims to describe the dimensions of power in the novel Negeri Senja by Seno Gumira Ajidarma. The method used is descriptive qualitative with the technique read, record, classify, and analyze. The Focus of research is the dynamics of power and the influence of this power in the novel Negeri Senja by Seno Gumira Ajidarma. The results research shows that in the novel power and knowledge have a relationship and relevance to each other. Power occurs through relationship and practise that produce knowledge, norms, and subjects so as to influence the dynamics of power in society. This novel depicts the narrative and identity in the Negeri Senja constructed by the rules. Who have power and operate in society. All data is he form of text narrates that power is everywhere, distributes, and manisfested in discourse, knowledge, and the regime of truth.